Imperial gullies : soil erosion and conservation in Lesotho - Showers, Kate Barger (Ohio University Press series in ecology and history., 2005)
Annotation "Once the grain basket for South Africa, much of Lesotho has become a scarred and degraded landscape. The nation's spectacular erosion and gullying have concerned environmentalists and conservationists for more than half a century. In Imperial Gullies, Kate B. Showers documents the truth behind this devastation." "Showers reconstructs the history of the landscape, beginning with a history of the soil. She concludes that Lesotho's distinctive erosion chasms, called dongas - often cited as a result of destructive land-use practices by African farmers - actually were caused by colonial and postcolonial interventions. The residents of Lesotho emerge as victims of a failed technology." "Imperial Gullies calls for an observational, experimental, and, most important, fully consultative and participatory approach to address Lesotho's serious contemporary problems of soil erosion. The first book to bring to center stage the historical practice of colonial soil science - and a cautionary tale of western science in unfamiliar terrain - it will interest a broad, interdisciplinary audience in African and environmental studies, social sciences, and history."--BOOK JACKET. Title Summary field provided by Blackwell North America, Inc. All Rights Reserved.